2017
DOI: 10.5039/agraria.v12i2a5429
|View full text |Cite
|
Sign up to set email alerts
|

Proporção e crescimento alométrico dos componentes não carcaça de cordeiros Texel abatidos com diferentes pesos

Abstract: RESUMOEste estudo teve como objetivo avaliar a proporção em relação ao peso de corpo vazio; e o crescimento alométrico dos componentes não constituintes da carcaça de cordeiros da raça Texel terminados em confinamento e abatidos com diferentes pesos. Foram utilizados 30 cordeiros machos, não castrados e nascidos de parto simples. Os cordeiros foram desmamados com aproximadamente 50 dias de idade, confinados individualmente e distribuídos em cinco tratamentos com seis repetições, sendo cada tratamento um peso p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Thus, as the study animals belonged to the same genetic pattern, the similarity between the variables is justified. Garcia et al (2014) and Carvalho et al (2017) described that the lung, heart, kidneys, diaphragm, bladder, spleen, blood, head, and paws develop early, surpassing the muscle and fat growth rate in the early stages of life, a situation that is reversed with the animal's growth, which explains the similarity between the weight of organs observed in the present study, since such organs are matured previously, regardless of the nutritional flow.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, as the study animals belonged to the same genetic pattern, the similarity between the variables is justified. Garcia et al (2014) and Carvalho et al (2017) described that the lung, heart, kidneys, diaphragm, bladder, spleen, blood, head, and paws develop early, surpassing the muscle and fat growth rate in the early stages of life, a situation that is reversed with the animal's growth, which explains the similarity between the weight of organs observed in the present study, since such organs are matured previously, regardless of the nutritional flow.…”
Section: Resultssupporting
confidence: 70%
“…The authors assumed that the increase might have been influenced by the increase in the content of NFC in the diet, inducing, through the production of volatile fatty acids, the growth of ruminal papillae, reticular ridges, and intestinal villi, resulting in more excellent absorption by the gastrointestinal tract and subsequent conversion in edible fabrics. Carvalho et al (2017) reported late allometric growth for the rumen, reticulum, and omasum, which may be affected by the aforementioned nutritional factor. However, the authors considered that the abomasum, small intestine, and large intestine are early heterogenic.…”
Section: Resultsmentioning
confidence: 99%
“…The variables abomasum (full and empty), rumen-full reticulum and the organs: lung/trachea, heart, spleen and tongue, were not influenced by the factors. Non-carcass components such as: omasum, rumen and reticulum, present late development, unlike the abomasum (early), and the percentages of some non-carcass components decrease with increasing live weight of animals [52]. However, the rumen-reticulum weight reached 0.80 kg, higher than those found by [53], with an average weight of 0.46 kg.…”
Section: Plos Onementioning
confidence: 82%
“…Sin embargo, la eficiencia productiva de los componentes del quinto cuarto pueden ser afectados por el estado nutricional de la dieta de los animales y el nivel de ingestión de alimentos (Carvalho et al, 2007), peso vivo (Carvalho et al, 2017), sexo (Peña et al, 2005), raza (Mendonça et al, 2003), sistemas de terminación (Camilo et al, 2012), entre otros. Aunque los corderos son caracterizados por su capacidad de convertir alimentos de baja calidad en proteínas de alto valor biológico, variaciones en la concentración de suplementos y especies de forrajes en la dieta pueden presentar respuestas distintas.…”
Section: Introductionunclassified